2013
DOI: 10.1016/j.cell.2013.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Hira-Dependent Histone H3.3 Deposition Facilitates PRC2 Recruitment at Developmental Loci in ES Cells

Abstract: SUMMARY Polycomb repressive complex 2 (PRC2) regulates gene expression during lineage specification through trimethylation of lysine 27 on histone H3 (H3K27me3). In Drosophila, polycomb binding sites are dynamic chromatin regions enriched with the histone variant H3.3. Here we show that in mouse embryonic stem cells (ESCs) H3.3 is required for proper establishment of H3K27me3 at the promoters of developmentally regulated genes. Upon H3.3 depletion, these promoters show reduced nucleosome turnover measured by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
329
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(388 citation statements)
references
References 47 publications
36
329
2
1
Order By: Relevance
“…Therefore, these results support a model whereby OGT binds and modifies HIRA and promotes HIRA-mediated nucleosome assembly of H3.3-H4 and cellular senescence. Histone variant H3.3 is assembled into nucleosomes at distinct chromatin domains in a replication-independent process (11)(12)(13)(14)(15)(16)(17)(18). In addition, histone H3.3 is mutated in high-grade pediatric brain tumors, chondroblastoma, and giant cell tumors (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these results support a model whereby OGT binds and modifies HIRA and promotes HIRA-mediated nucleosome assembly of H3.3-H4 and cellular senescence. Histone variant H3.3 is assembled into nucleosomes at distinct chromatin domains in a replication-independent process (11)(12)(13)(14)(15)(16)(17)(18). In addition, histone H3.3 is mutated in high-grade pediatric brain tumors, chondroblastoma, and giant cell tumors (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, along with H4, canonical histone H3.1/H3.2 is deposited by the histone chaperone CAF-1 during S phase, whereas H3.3 is assembled into nucleosomes at pericentric and telomeric regions by DAXX/ATRX, and at genic regions by the HIRA complex (11)(12)(13)(14)(15)(16)(17)(18). In addition to histone chaperones, posttranslational modifications on newly synthesized histones impact nucleosome assembly, in part by regulating the interactions between histone chaperones and their histone cargo.…”
mentioning
confidence: 99%
“…It is thus enriched in areas of increased nucleosome turnover including transcribed genes but is also found in silent regions including pericentromeric heterochromatin and telomeres (Szenker et al , 2011). H3.3 is essential for development as it is necessary for proper trimethylation of H3K27 at genes regulated by the polycomb‐repressive complex 2 (Banaszynski et al , 2013). Complete absence of H3.3 in mice thus results in peri‐implantation lethality (Jang et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that maternal H3.3 is specifically involved in the reactivation of gene expression in SCNT embryos during reprogramming and may not be required for the maintenance of gene expression, consistent with our observation of the maintenance of self-renewal in H3.3KD ESCs. 34 RNA-seq confirmed that many key pluripotency genes (e.g., Oct4, Nanog) fail to become activated upon SCNT in the absence of H3.3.…”
Section: Reactivation Of Pluripotencyassociated Genes Is Dependent Upmentioning
confidence: 94%